Caring for AML Patients During the COVID-19 Crisis: An American and Italian Experience - Wilde, Lindsay; Isidori, Alessandro; Keiffer, Gina; Palmisiano, Neil; Kasner, Margaret (Frontiers in Oncology, 2020)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the subsequent pandemic has impacted every aspect of oncology care worldwide. Healthcare systems have been forced to rapidly change practices in order to maximize the safety of patients and healthcare providers and preserve scare resources. Patients with acute myeloid leukemia are at increased risk of complications from SARS-CoV-2 not only due to immune compromise related to the malignancy, but also due to the acuity of the disease and intensity of treatment. These issues have created unique challenges during this difficult time. In this article, we present the approaches taken by two groups of hematologist/oncologists, one in the United States and one in Italy, who have been caring for AML patients in the face of the pandemic.